The Influence of E-Module Based on Contextual Approaches on Historical Thinking Skills - Raharjo, Tiur Nurmayany; Mulyana, Agus; Sumantri, Yeni Kurniawati (Yupa: Historical Studies Journal, 2024)
This research is motivated by Kurikulum Merdeka in History lessons which contains achievements to be able to contextualize events that occurred in the past. The ability of teachers who have now developed by having the ability to create and use electronic-based teaching materials can develop electronic-based teaching materials containing historical material that is linked to contextual issues. Seeing this, the researcher conducted a quasi-experimental study aimed at analyzing the influence of e-modules based on a contextual approach to historical thinking skills. The researcher saw this influence by using a quasi-experiment with a time series design conducted at SMA Negeri 26 Bandung. The results of the study showed that e-modules based on a contextual approach can show an influence on historical thinking skills with a moderate increase in the category.